Investigating 16th century knitting with citizen science: An archaeological experiment into fleece and fulling - Malcolm-Davies, Jane; Mearns, Rosalindm (Archaeological Textiles Review, 2018)
An archaeological experiment was undertaken as part of the Knitting in Early Modern Europe (KEME) project to determine the best modern match for the fleece used in surviving 16th century knitted caps. Circular test swatches, known as ‘swircles’, were created by volunteers from a variety of fleece. The experiment demonstrated that, through citizen science, members of the public can contribute meaningfully to academic textiles research. It recorded a number of useful insights into the process of involving volunteers in experimental archaeology. The aim was to recreate the thick nap observed on the extant cap linings. Half the swircles were hand-fulled and brushed to raise a nap by the volunteers. The nap raised from a Wensleydale yarn most closely resembled the length of the preserved naps but Bluefaced Leicester fleece provided a softer and more even coverage. No tested fleece provided a combination of these features to sufficiently mimic the extant nap.